2017
DOI: 10.1038/s41598-017-11096-1
|View full text |Cite
|
Sign up to set email alerts
|

eIF4B phosphorylation at Ser504 links synaptic activity with protein translation in physiology and pathology

Abstract: Neuronal physiology requires activity-driven protein translation, a process in which translation initiation factors are key players. We focus on eukaryotic initiation factor 4B (eIF4B), a regulator of protein translation, whose function in neurons is undetermined. We show that neuronal activity affects eIF4B phosphorylation and identify Ser504 as a phosphorylation site regulated by casein kinases and sensitive to the activation of metabotropic glutamate receptors. Ser504 phosphorylation increases eIF4B recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 70 publications
(81 reference statements)
0
20
0
Order By: Relevance
“…However, no significant changes were observed for phospho-eIF4B at Ser422, an inhibitory modification [69, 77], in four C9+ derived cell lines versus five control cell lines. Extended analyses are needed to increase the sample size and to test for eIF4B phosphorylation at other marks [9, 89]. Overall, we hypothesize that eIF4H is downregulated as the result of compensatory mechanisms: cells may actively downregulate eIF4H to reduce expression of toxic GR dipeptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant changes were observed for phospho-eIF4B at Ser422, an inhibitory modification [69, 77], in four C9+ derived cell lines versus five control cell lines. Extended analyses are needed to increase the sample size and to test for eIF4B phosphorylation at other marks [9, 89]. Overall, we hypothesize that eIF4H is downregulated as the result of compensatory mechanisms: cells may actively downregulate eIF4H to reduce expression of toxic GR dipeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, yeast and flies (see Fig. 3b) with downregulated eIF4B or eIF4H are viable [2, 15, 33] and eIF4H +/− mice do not have notable deficits [11]; although eIF4B and eIF4H have been suggested to be important for brain development [9, 11, 20, 67]. The downstream consequences of eIF4H downregulation in C9+ ALS/FTD may be broader than simply altering RAN-translation as depletion of eIF4B and eIF4H in cultured cells has been shown to induce stress granule formation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Akt signaling is critical for activity-dependent dendritic translation [ 26 , 27 , 31–33 ]. Neuronal activity robustly stimulates local Akt phosphorylation and signaling, which allows the initiation of synaptic protein translation [ 28 , 62 ]. In the present study, we observed that the loss of activity-dependent translation induced by neonatal maternal separation was accompanied by diminished expression of active phosphorylated Akt (at pThr308 and PSer473 Akt) in synaptoneurosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-induced eIF4B phosphorylation correlates with an observed increase in translation [33], while heat shock and serum starvation cause its dephosphorylation. Identified phosphorylation sites include Ser422 (phosphorylated by S6K and p90 ribosomal protein S6 kinase (RSK) [34] or by PKB [35]), Ser406 (depends on MEK and mTOR activity [35]), Ser496 (by Pim1 and Pim2 kinases [36]), and Ser504 (by casein kinase [37]). Phosphorylation of these residues was demonstrated to modulate eIF4B translational activity.…”
Section: Regulation Of Eif4f Activity By Ser/the Phosphatasesmentioning
confidence: 99%